The Effect of Vocabulary Journals on Eleventh-Grade Students’ Vocabulary Mastery at SMK Trisakti Jaya Bandar Lampung - Fitriana, Shafa; Nurchurifiani, Eva; Herlisya, Destia (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
This research aimed to determine the influence of using vocabulary journals on students’ vocabulary mastery at the eleventh grade of SMK Trisakti Jaya Bandar Lampung in the academic year 2024/2025. The research used a quantitative method with a quasi-experimental design. The sample consisted of two classes: XI AKL as the experimental class (16 students) and XI MM as the control class (22 students), totalling 38 students. The experimental class was taught using vocabulary journals, while the control class was taught using conventional media. The data were collected through pre-test and post-test and analyzed using SPSS, including tests of normality, homogeneity, and an independent sample t-test. The result of the Independent Sample t-Test showed a significance value (Sig. 2-tailed) of 0.000, which is less than α = 0.05. This indicates a significant difference in vocabulary mastery between the experimental and control classes. The mean difference was 15.523, with a 95% confidence interval ranging from 10.564 to 20.481. Therefore, H₀ is rejected and Ha is accepted. It can be concluded that the use of a vocabulary journal has a significant influence on students’ vocabulary mastery. The average post-test score of the experimental class was 79.25, which was higher than the control class’s score of 63.73. This indicates that students taught using vocabulary journals achieved better vocabulary mastery than those taught using conventional media.